High Temperature Spectrally Selective Solar Absorbers Using Plasmonic AuAl2:AlN Nanoparticle Composites. Issue 10 (7th September 2017) - Bilokur, Maryna; Gentle, Angus; Arnold, Matthew D.; Cortie, Michael B.; Smith, Geoffrey B.
Abstract : Advanced solar energy collectors require the use of thermally stable and spectrally selective coatings in order to boost absorption of radiant energy. Here, it is shown that incorporation of plasmonically resonant Au and AuAl2 nanoparticles into multilayer coatings based on AlN provides strong and stable absorption across the solar spectrum at temperatures between RT and 500 °C. Optical properties at operating temperature are verified using in situ measurements. Solar absorptance of 92–97% is available in the as‐deposited films, which are comprised of layers of Al, Au:AlN, AlN, and SiO2 . Annealing at the operating temperature of ∼500 °C causes the conversion of the elemental Au to the intermetallic compound AuAl2, but the good solar absorbing performance is retained. The additional Al that reacts with the Au nanoparticles to form the AuAl2 diffuses up from the reflective Al substrate used. Enhanced NIR solar absorptance post‐annealing is accompanied by a tolerable small rise in thermal emittance. Formation of AuAl2 :AlN also prevents undesired Au nanoparticle agglomeration above 500 °C. This suggests that AuAl2 :AlN nanoparticle composites are excellent candidates for solar thermal applications up to about 500 °C. Abstract : Thermally stable coatings for solar thermal devices may be obtained by dispersing AuAl2 intermetallic nanoparticles within a refractory AlN matrix. These provide high efficiency absorption at peak solar wavelengths but low radiative heat loss in the infrared region.